Social Dimensions of the IMF'S Policy Di Alogue (Reprinted 1998) P047. (Pamphlet Series, 1995)
This pamphlet focuses on the IMF's role in social policy advice. First,the evolution of the IMF's involvement in social issues is traced,and the lessons that can be drawn from this experience, includingpolicy implications, are outlined. This is followed by an elaboration of the social dimensions of IMF policy advice to member countries underits two major activities: surveillance of economic policies and financial support for adjustment programs. The IMF's collaboration onsocial issues with the World Bank and UN agencies is examined, and theconclusion focuses on ways to further strengthen the IMF's contributionto social development.